DETERMINATION OF COST PRODUKSIDENGAN Activity Based Costing SYSTEM TO MANUFACTURE OF BAMBOO CRAFT KARTI AJI - Ariyanto, Harnawan (Accounting, 2010)
" Sleman Regency is a central area with craft industries which various kinds. One of the famous craft in Sleman regency is bamboo handicraft industry, where the resulting products have been exported to overseas. Most of the bamboo craft industry in Sleman district determines the cost of their products with conventional systems, so that decision-making about pricing based on inaccurate cost information. This happens because they still do not understand about the cost of the product by observing activity. bamboo handicraft companies Karti Aji factory overhead charge into a product with an allocation of raw materials by using a system that is believed taksiran.The calculation is a system which is believed to be more accurate in determining the cost of the product that is with Activity Based Costing System (ABC system). ABC systems arise as a result of the information management needs will be capable of reflecting the cost of resource consumption in various activities in generating produk. Using the ABC system revealed that over the imposition of BOP per unit on the basis of raw material cost (estimated) led to the imposition of costs of production are too high (overcost) as applied to the product box by box (5.26%) and woven bags (2, 97%) than it reveals that the company charged the cost of production to the product is too low (undercost), namely the hood of food products amounted to (5.81%)."